Evaluation of stroke volume variation and pulse pressure variation as predictors of fluid responsiveness in patients undergoing protective one-lung ventilation - Fu, Qiang; Duan, Mingda; Zhao, Feng; Mi, Weidong (Drug Discoveries & Therapeutics, 2015)
In order to investigate whether the hemodynamic indices, including stroke volume variation (SVV) and pulse pressure variation (PPV) could predict fluid responsiveness in patients undergoing protective one-lung ventilation. 60 patients scheduled for a combined thoracoscopic and laparoscopic esophagectomy were enrolled and randomized into two groups. The patients in the protective group (Group P) were ventilated with a tidal volume of 6 mL/kg, an inspired oxygen fraction (FiO2) of 80%, and a positive end expiratory pressure (PEEP) of 5 cm H2O. Patients in the conventional group (Group C) were ventilated with a tidal volume of 8 mL/kg and a FiO2 of 100%. Dynamic variables were collected before and after fluid loading (7 mL/kg hydroxyethyl starch 6%, 0.4 mL/kg/min). Patients whose stroke volume index (SVI) increased by more than 15% were defined as responders. Data collected from 45 patients were finally analyzed. Twelve of 24 patients in Group P and 10 of 21 patients in Group C were responders. SVV and PPV significantly changed after the fluid loading. The receive operating characteristic (ROC) analysis showed that the thresholds for SVV and PPV to discriminate responders were 8.5% for each, with a sensitivity of 66.7% (SVV) and 75% (PPV) and a specificity of 50% (SVV) and 83.3% (PPV) in Group P. However, the thresholds for SVV and PPV were 8.5% and 7.5% with a sensitivity of 80% (SVV) and 90% (PPV) and a specificity of 70% (SVV) and 80% (PPV) in Group C. We found SVV and PPV could predict fluid responsiveness in protective one-lung ventilation, but the accuracy and ability of SVV and PPV were weak compared with the role they played in a conventional ventilation strategy.